2017
DOI: 10.3389/fphar.2016.00520
|View full text |Cite
|
Sign up to set email alerts
|

N-n-butyl Haloperidol Iodide Protects against Hypoxia/Reoxygenation Injury in Cardiac Microvascular Endothelial Cells by Regulating the ROS/MAPK/Egr-1 Pathway

Abstract: Endothelium dysfunction induced by reactive oxygen species (ROS) is an important initial event at the onset of myocardial ischemia/reperfusion in which the Egr-1 transcription factor often serves as a master switch for various damage pathways following reperfusion injury. We hypothesized that an intracellular ROS/MAPK/Egr-1 signaling pathway is activated in cardiac microvascular endothelial cells (CMECs) following hypoxia/reoxygenation (H/R). ROS generation, by either H/R or the ROS donor xanthine oxidase-hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 27 publications
2
24
0
Order By: Relevance
“…CMECs were identified by flow cytometry using antibody against CD31 and VWF/Factor VIII, which are constitutively expressed on the surface of CMECs. Hypoxia was induced as before with some modifications . Briefly, CMECs were cultured in hypoxia solution in an air‐tight chamber saturated with pure N 2 at 37°C for 2 hours; the culture conditions were then returned to normal for 2 hours of reoxygenation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CMECs were identified by flow cytometry using antibody against CD31 and VWF/Factor VIII, which are constitutively expressed on the surface of CMECs. Hypoxia was induced as before with some modifications . Briefly, CMECs were cultured in hypoxia solution in an air‐tight chamber saturated with pure N 2 at 37°C for 2 hours; the culture conditions were then returned to normal for 2 hours of reoxygenation.…”
Section: Methodsmentioning
confidence: 99%
“…Hypoxia was induced as before with some modifications. 17 Briefly, CMECs were cultured in hypoxia solution in an air-tight chamber saturated with pure N 2 at 37°C for 2 hours; the culture conditions were then returned to normal for 2 hours of reoxygenation.…”
Section: Cell Culture and Treatmentmentioning
confidence: 99%
“…Numerous studies have shown that reactive oxygen species (ROS)-induced oxidative stress is key to myocardial I/R injury ( Murphy and Steenbergen, 2008 ; Radak et al, 2011 ; Minamino, 2012 ). Both Egr-1 and ROS are closely related to I/R injury, and our previous research has shown that the ROS/MAPK/Egr-1 signaling pathway is activated during hypoxia/reoxygenation (H/R) models of myocardial and cardiac microvascular endothelial cells (CMEC) ( Zhang et al, 2015 ; Lu S. et al, 2016 ). Bek’s group reported that over-expressed Egr-1 in proximal tubule epithelial cells downregulates expression of Cu/Zn-SOD and Mn-SOD, resulting in increased tissue ROS ( Bek et al, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…Epigenetics refers to the modulation of gene expression via post-translational modification of protein complexes associated with DNA, without changing the DNA sequence (16,17). Among the several protein/histone modifications are acetylation, methylation, phosphorylation, ubiquitination, and sumoylation (17,18).…”
mentioning
confidence: 99%